Projected changes of future climate extremes in Malaysia - Meng, Sei Kwan; Fredolin T. Tangang,; Liew, Juneng (Universiti Kebangsaan Malaysia, 2013)
Mitigating and adapting to the impacts of climate change at regional level require downscaled projection of future climate states. This paper examined the possible changes of future climate extremes over Malaysia based on the IPCC SRES A1B emission scenario. The projected changes at 17 stations were produced by bias correcting the UKMO PRECIS downscaling simulation output. The simulation expected higher probability of rainfall extreme occurrences over the west coast of Peninsular Malaysia during the autumn transitional monsoon period. In addition, possible early monsoon rainfall was projected for certain stations located over East Malaysia. The simulation also projected larger increase of warm temperature extremes but smaller decrease of cold extremes, suggesting asymmetric expansion of the temperature distribution. The impact of the elevated green house gases (GHG) is higher in the night time temperature extremes as compared to the day time temperature extremes. The larger increment of warm night frequencies as compared to the warm day suggests smaller diurnal temperature ranges under the influence of higher greenhouse gases. Stations located in East Malaysia were projected to experience the largest increase of warm night occurrence.